The physical and mental health effects of housing homeless people: A systematic review. (22nd August 2021) - Onapa, Hebaat; Sharpley, Christopher F.; Bitsika, Vicki; McMillan, Mary E.; MacLure, Katie; Smith, Lee; Agnew, Linda L.
Abstract: Housing is a significant determinant of health and is widely accepted as a key solution to address some of the health disparities that exist among the homeless. It is estimated that 150 million people worldwide are homeless, and approximately 1.8 billion lack adequate housing. However, understanding of how housing has a positive impact on the health of the homeless remains unclear and underdeveloped. This systematic review investigates intervention studies that report on the physical and mental health effects of housing homeless persons. A search of PubMed, PsycINFO, EBSCOHost‐Academic Search Complete and the Cochrane Library was conducted for peer‐reviewed articles published in English from 1999 to 2020 that had a combination of at least one housing intervention and health outcome, with a homeless sample. Three previous reviews and 24 studies were included for analysis. Most of the studies ( n = 20) encompassed permanent supportive housing interventions that emphasised placing homeless people with mental illness directly into affordable housing with access to support services. The primary health outcomes reported were general physical and mental health, well‐being, and quality of life. Despite inconsistent findings and significant issues identified in the reviewed literature, housing (in the short term) improves some aspects of health in homeless populations with human immunodeficiency virus, anxiety and depression.